Report on currency and finance 1988-89 : Volume 1 (India : Department of Economic Analysis and Policy, Reserved Bank of India, 1989)
The report covers eleven chapters. Chapter I, Review and Outlook. Chapter II, National Income, Saving and Investment. Chapter III, Agricultural Output. Chapter IV, Industrial Production. Chapter V, Price Trends and Price Policy. Chapter VI, Monetary Developments. Chapter VII, Banking Developments. Chapter VIII, Fiscal Developments. Chapter IX, Capital Market. Chapter X, Developments in India's Foreign Trade. Chapter XI, Balance of payments and International Monetary Developments.
Economic Review
rpm 09/05/2018
Loans
Keywords: Banks and banking